CORRELATION DIVERSITY OF BACTERIA TO SECONDARY META BOLITES Nephthea spp. from SERIBU ISLANDS NATIONAL PARKS WATERS - Gintung Patantis; Hedi Indra Januar; Ekowati Chasanah (Widyariset, 2012)
Bioactive compounds from biota on coral reef is potentially of plasma nutfah that has high economic value.Their existence was influenced by the microbes which associated with them and the environmental conditions. Theaim of the research was to analyze the correlation between the diversity of bacteria and secondary metabolitesNephthea spp. collected from Seribu Islands National Parks (TNKpS). The analysis of bacteria diversity performedby Terminal Restriction Fragment Length Polymorphism (T-RFLP) and secondary metabolites used High PerformanceLiquid Chromatography (HPLC). The results of study showed that the range of diversity index (H), richness(R), and evenness index (E) of bacteria were 1,47–0,88; 13–3; 0,84–0,43. And the for the secondary metabolitesthe range were 2,21–1,12; 20-5; 0,95–0,63. Further study showed that there was a significant correlation (R =0.96 at p< 0.01) between bacteria and secondary metabolites group richness. The area which high diversity ofbacteria and secondary metabolites were within central and southern TNKpS waters. This results were in line withthe best water quality in these areas.